JUNG'S PSYCHOLOGICAL TYPES AND CHARACTERISATION IN ALEX LAGUMA’S LITERARY WORKS - Garuba, Issa Omotosho (University of Muhammadiyah Malang, 2020)
Characterisation has immense influence on the study of literature, because it is as one of the determinants in measuring the quality of a narrative. Thus, assessing this aspect of a narrative, especially when dealing with characters in a racist narrative, requires an encompassing analytical approach. Hence, this paper is aimed atanalysing the psychological impulses that underlying the personality formations of the black characters in Alex La Guma’sA Walk in the Night and In the Fog of the Season’s End. In which, it adopts Carl Gustav Jung’s Psychological Types. The choice of this psychoanalytical tool is informed by the fact that, of all the psychological discoveries of Jung, the psychological types or the psychology of individuation has been acknowledged as his most significant discovery in psychoanalysis which has not attracted the literary critical attention, especially in terms of character analysis. To this end, therefore, the study attempts to establish the two categories of the reactions identified by Jung, namely introversion and extraversion, using the two Alex La Guma’sfictions.In addition, through the psychological complexities of the characters, ultimately, it is revealed that the extreme reactions are the products of individual innate tendencies, devoid of the social or the racial affiliations.